STRATEGI PENGEMBANGAN DAYA TARIK WISATA SUNGAI TELAGA WAJA SEBAGAI DESTINASI WISATA KELUARGA DI KABUPATEN KARANGASEM - Putu Agus Prayogi; Ni Putu Putri Widyaningsih (Universitas Triatma Mulya, 2023)
Telaga Waja River is one of natural attractions located in Karangasem, Bali. This tourist destination has interesting potential based on the natural resources that could be developed into family attractions. This study aimed to analyze how the Telaga Waja River in Tangkup Village can develop into an alternative family tourism in Bali. In addition, the purpose of this research was to identify the tourist attractions in Telaga Waja River as well as the alternative for its development for families. Data collected by observation and interview and then analize with descriptive qualitative approach while data sources are primer and secondary source. The research found out that Telaga Waja River has sufficient 4A tourism components (attraction, amenities, accessibility, ancillary) but needs to be developed to optimize the attraction or tourist activities for tourists, especially families. The attraction that could be added such as camping site, gathering area, fishing spot, play ground for children. Those alternative attractions need serious support from the village leader, training for local people (human recources), strong planning as well as community involvement and support to implement the community-based tourism in Tangkup Village Karangasem.